Précision et reproductibilité du mesurage de la turbidité des eaux résiduaires urbaines - Ruban, G.; Bertrand-Krajewski, J.L.; Chebbo, G.; Gromaire, M.C.; Joannis, C. (2ème Conférence SHF/ASTEE/GRAIE Autosurveillance, diagnostique permanent et modélisation des flux polluants en réseaux d’assainissement urbains., 2005)
In order to analyse the representativity of samplers taken on the sites of the OPUR, 2 approaches were followed: theoretical and experimental. The theoretical approach has permit to respect 7 criteria out of 9 recommended at the time of the choice and the installation of an automatic sampler. The experimental tests showed a satisfactory homogeneity of concentrations in the various sections of measurement, a good representativity of samplings when the pipes are clean a contamination of samples by clogging of samplings pipes because of erosion of biofilms, an influence of temperature and shelf life on the samples intended for the analysis of ammonium and dissolved parameters. The contamination will be eliminated by samplings wastewater then clean water before each measurement campaign and by setting out of the water of samplings pipes. All the analyses will be carried out immediately.